La diversitá cloroplastica delle querce italiane: evidenze di una maggiore ricchezza genetica nelle popolazioni meridionali e insulari - Fineschi, S; Vendramin, G G (iForest - Biogeosciences and Forestry, 2004)
Results of the analysis of non-coding regions of the chloroplast genome in Italian population of deciduous oaks (subgenus Quercus) and holm oak (subgenus Scleropyllodris) are reported. Deciduous oak revealed the occurrence of six chloroplast haplotypes, differently distributed in the single geographic areas (northern, central, and southern Italy, and major islands). Moreover, most of the present Italian oak populations seems to derive from two major refugia, located in Sicily and in the Balkans, respectively. The most likely migration dynamics from the refugia towards the central and northern part of the peninsula are discussed. Migration pathways resulted to have been different in the various geographic areas. The presence of an endemic haplotype in Sardinia and Corsica was considered of particular interest. In Italian holm oak populations eight haplotypes were detected, six of them in Sicily. Five out of six Sicilian haplotypes resulted to be endemic. The Italian peninsula was colonized by two major haplotypes, one of them originating from Sicily. Results on deciduous oaks and holm oak in Italy highlight the important role played by the populations from the south and from the major islands in the colonization the Italian peninsula after the last ice age.
Keywords: Chloroplastic Diversity; colonization; conservation; glacial refugia; phylogeography; Quercus